Getting into the act : women playwrights in London, 1776-1829 - Donkin, Ellen, 1949- (Routledge, 1995)
Getting Into the Act is a vigorous and refreshing account of seven female playwrights who, against all odds, enjoyed professional success in the late eighteenth and early nineteenth century. Ellen Donkin relates fascinating, disturbing tales about the male theatre managers to whom they were indebted, and the trials and prejudices they endured, ranging from accusations of plagiarism to sexual harassment. This scarred turbulent early history still resonates in the late twentieth-century. The current ratio of female to male playwrights is virtually unchanged. Old patterns of male control persist, and playwriting continues to be a hazardous occupation for women. But within these scarred earlier histories there are equally powerful narratives of self-revelation, endurance, and professional triumph that may point to a new way forward. Getting Into the Act is entertaining and informative reading for anyone, from scholar to general reader, who is interested in the history and gender politics of the stage.